Digitales Verwaltungshandeln Rechtliche Aspekte der Digitalisierung in der öffentlichen Verwaltung - Plattner, Roger (sui generis Verlag, 2021)
"At a time when most everyday tasks can be performed online, public administration is also facing increasing demands in terms of accessibility, availability and simplification of its services. For this reason, numerous administrative services have been digitized in recent years under the term ""e-government"". In addition to all the positive aspects, this digitization is also associated with challenges and risks for the legal position of private individuals. This monograph is intended to contribute to answering the question of how the changes in the field of administrative action that accompany digitization are to be assessed in legal terms. On the one hand, technologies and phenomena that are already being used in the actions of public administration are examined for their compatibility with the existing legal framework. On the other hand, emerging future developments are highlighted and examined with a critical eye on possible legal problems. Translated with www.DeepL.com/Translator (free version)"